The Effect of CEO Education, CEO Tenure, Company Risk, and Environmental Performance on Company Value - Khawarizmi Aulia Robbani; Hasnawati, Hasnawati; R. Rosiyana Dewi; Marieta Ariani; Doris Madhi; Salsabila Alya (Indonesian Management and Accounting Research, 2024)
This study aims to determine the effect of CEO education, CEO tenure, company risk, and environmental performance on company value. This research used a purposive sampling method with the following criteria: the companies must not be delisted or suspended by the IDX, they must have complete background financial statement data and additional information regarding the educational background and tenure. The 294 samples observed in this research came from 116 companies listed on the Indonesia Stock Exchange that have an environmental management assessment (PROPER) report for the period 2018 – 2020. The research data were collected through the Indonesia Stock Exchange website, the company’s website, and the PROPER report issued by Indonesia’s Ministry of Environment and Forestry. SPSS 27 was used to process the data. The research found that CEO tenure has a negative effect on company value, while environmental performance positively affects company value. However, CEO education and company risk do not have a significant effect on company value. This research provides managerial contributions to investors and management, suggesting that they need to pay attention to aspects of CEO tenure and environmental performance because these factors were responded to by the market.